Analysis Of Foreign Language Courses in Modern Higher Education - Mamajanova G’uncha Khamraevna (Genius Journals, 2021)
This article highlights the importance attached to foreign languages in the Republic of Uzbekistan and the innovative technologies needed to study them.
Keywords: Foreign language; game; innovative technology; technological tools